2018
DOI: 10.1371/journal.pone.0200312
|View full text |Cite
|
Sign up to set email alerts
|

Tracing anthropogenic inputs in stream foods webs with stable carbon and nitrogen isotope systematics along an agricultural gradient

Abstract: Stable carbon (13C) and nitrogen isotopes (15N) are useful tools in determining the presence of agricultural influences in freshwater ecosystems. Here we examined δ15N and δ13C signatures in nitrate, fish, and mussel tissues, from rivers in Southern Ontario, Canada, that vary in their catchment proportion of agriculture land use, nutrients and organic matter quality. We found comparatively 15N-enriched δ15N values in animal tissues and dissolved nitrates, relative to expected values characterized by natural so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Anthropogenic activities (particularly land development and agricultural practices) can contribute nitrogen sources that enter the local environment and impact the nitrogen isotope composition of primary producers. This effect is particularly pronounced in modern wetland habitats 45 .…”
Section: Introductionmentioning
confidence: 97%
“…Anthropogenic activities (particularly land development and agricultural practices) can contribute nitrogen sources that enter the local environment and impact the nitrogen isotope composition of primary producers. This effect is particularly pronounced in modern wetland habitats 45 .…”
Section: Introductionmentioning
confidence: 97%
“…More recently, efforts have been made to extend these results to food web structure and function (e.g. [12][13][14]). While studies have shown that increased nutrients and riparian removal can alter energy flows into ecosystems, it is not yet well understood how different forms of local agriculture mediate stream food web responses in agriculturally dominated watersheds [15].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, riparian land-cover vegetation type has been linked to effects on food-chain length (Fraley et al 2018), but it is unclear what mechanisms influence this. For example, does per cent catchment pastoral cover affect fish trophic position indirectly through algae and invertebrate consumers, or are effects due to isotopic enrichment from nitrate runoff influencing stable isotope (SI)derived measures of trophic position (Lake et al 2001;Anderson & Cabana 2005;Clapcott et al 2012;Lee et al 2018)? Therefore, understanding the mechanisms controlling freshwater trophic structure could give managers a tool for measuring and addressing effects of perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…2012; Lee et al . 2018)? Therefore, understanding the mechanisms controlling freshwater trophic structure could give managers a tool for measuring and addressing effects of perturbations.…”
Section: Introductionmentioning
confidence: 99%